2017
DOI: 10.1063/1.4975377
|View full text |Cite
|
Sign up to set email alerts
|

Near-edge X-ray refraction fine structure microscopy

Abstract: See supplementary material for a brief description of the experimental system and data analysis protocol. Soft X-ray ptychographic microscopy was carried out at beamline 5.3.2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…At each energy point and tilt angle, the camera background signal is measured with the beamline shutter closed, and the background is removed in subsequent data processing. 31,55 Ptychographic images were reconstructed using 500 iterations of the relaxed averaged alternating reflection reconstruction algorithm implemented in the SHARP ptychography code developed by the Center for Applied Mathematics for Energy Research Applications. 66 MethodsFourier Ring Correlation.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…At each energy point and tilt angle, the camera background signal is measured with the beamline shutter closed, and the background is removed in subsequent data processing. 31,55 Ptychographic images were reconstructed using 500 iterations of the relaxed averaged alternating reflection reconstruction algorithm implemented in the SHARP ptychography code developed by the Center for Applied Mathematics for Energy Research Applications. 66 MethodsFourier Ring Correlation.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The FRC calculation is explained in detail in the Supplementary Materials. The quantity analyzed is the scattering contrast, , where and are the reconstructed maps of the optical density and phase and is similarly linear with material thickness ( 22 ). Figure 1B shows that the FRC maintains a high value out to the full NA, which reaches a full-period spatial frequency of 0.17 nm −1 , corresponding to 6-nm oscillation periods.…”
Section: Resultsmentioning
confidence: 99%
“…The overall chemical maps are in qualitative agreement, but the ptychographic chemical map displays nanoscale chemical phases in the particle interior, which are not visible in conventional imaging mode. In this case, the chemical maps are obtained with a linear combination of reference spectra measured from nanoparticles of pure materials ( 22 ); thus, they represent quantitative composition with red being FePO 4 and green being LiFePO 4 . The radiation dose delivered to the sample is estimated in fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, as this work has demonstrated, one major benefit of X-ray linear dichroic ptychography is that strong polarization-dependent phase contrast is also available when imaged at the off-resonant energy. Benefits of off-resonance, dose-efficient imaging have been reported (48,55), in which the large phase shifts and strong energy dependence near atomic resonances play an important role in achieving high spatial resolution. It was observed that the maximum resolution peak falls at the energy of the most negative phase shift relative to vacuum, which yields the maximum phase…”
Section: Discussionmentioning
confidence: 99%